Clinical features of drug-induced Parkinsonism - Nobuko Shiraiwa; Akira Tamaoka; Norio Ohkoshi (MDPI AG, 2018)
Drug-induced Parkinsonism is often reversible after withdrawal of the causative drug. Its clinical course, however, is not well understood, as the majority of cases are caused by drugs prescribed by departments outside of neurology. We reviewed 21 cases of drug-induced parkinsonism for several factors, including age, sex, causative drug and reason for prescription, department by which it was prescribed, and outcome. The age at onset ranged from 40 to 87 years, with an average Hoehn and Yahr Scale score of 4, indicating severe disability. Sulpiride was the most commonly observed causative drug (71.4%). All causative drugs were prescribed in non-neurological departments and over one half were prescribed in non-psychiatric departments; most were prescribed to treat depression or abdominal discomfort. Ten patients (48%) were previously diagnosed with a neuromuscular disease, including cerebrovascular diseases and Parkinson's disease. Recovery was observed in 15 cases (71%) after withdrawal of the causative drug, but lingering symptoms were observed in the remaining cases. It is suggested that physicians should be more cautious of Parkinsonian side effects when prescribing such drugs.